Inteligencia artificial en la producción audiovisual: caso Roberto MTZ - Ordoñez Bermeo, Fabian Joel (Machala : Universidad Técnica de Machala, 2025)
To what extent can AI replicate or even enhance the creative process without eliminating the human touch that characterizes audiovisual creations? In a world where personalization is key to success, AI has the potential to change the rules of the game for independent content creators. This study seeks to analyze how Roberto MTZ integrates AI tools into his workflow to optimize processes such as editing, content generation, and interaction with his audience. Through a qualitative analysis, the impact of these technologies on the quality and efficiency of his production workflow, as well as on his engagement with his followers, will be identified. This research will not only fill a significant gap in the understanding of AI use by independent creators but will also offer valuable and significant patterns for other content producers looking to improve their practices using emerging technologies. To address this issue, it is essential to conduct a thorough investigation that not only allows for an understanding of the tools and strategies used by MTZ but also analyzes how these technologies affect the results in terms of quality, efficiency, and viewer experience. Furthermore, it will be crucial to explore the broader implications of this case for the digital audiovisual production industry, by providing valuable insights into how individual creators are leveraging the capabilities of AI to enhance their work and connect with their audience. In conclusion, the use of AI in the audiovisual production of YouTubers like Roberto MTZ offers a fertile field for research, as it addresses key questions about the intersection of technology, creativity, and interaction in the digital world. This study will not only contribute to the knowledge of emerging technologies in audiovisual production but will also offer a framework for other international or national creators seeking to optimize their processes using AI.
¿Hasta qué punto puede la IA replicar o incluso mejorar el proceso creativo, sin eliminar el toque humano que caracteriza a las creaciones audiovisuales? En un mundo donde la personalización es clave para el éxito, la IA tiene el potencial de cambiar las reglas del juego para los creadores de contenido independiente. Este estudio busca analizar cómo Roberto MTZ integra herramientas de IA en su flujo de trabajo para optimizar procesos como la edición, la generación de contenido y la interacción con su audiencia. A través de un análisis cualitativo, se identificará el impacto de estas tecnologías en la calidad y eficiencia de su producción en cuanto a su flujo de trabajo, así como en la interacción que tiene con sus seguidores. Esta investigación no solo llenará una brecha significativa sobre el uso de IA por creadores independientes, sino que también ofrecerá patrones valiosos y significativos para otros productores de contenido que busquen mejorar sus prácticas utilizando tecnologías emergentes. Para abordar este problema, es esencial realizar una investigación exhaustiva que permita solo entender las herramientas y estrategias utilizadas por MTZ, sino también analizar cómo estas tecnologías afectan los resultados en términos de calidad, eficiencia y experiencia del espectador. Además, será crucial explorar las implicaciones más amplias de este caso para la industria de la producción audiovisual digital, al proporcionar sentido de valor sobre cómo los creadores individuales están aprovechando las capacidades de la IA para mejorar su trabajo y conectar con su audiencia. En conclusión, el uso de la IA en la producción audiovisual de youtubers como Roberto MTZ ofrece un campo fértil para la investigación, pues aborda cuestiones clave sobre la intersección de la tecnología, la creatividad y la interacción en el mundo digital. Este estudio no solo contribuirá al conocimiento sobre las tecnologías emergentes en la producción audiovisual, sino que también ofrecerá un marco para otros creadores internacionales o nacionales que buscan optimizar sus procesos utilizando la IA.
Keywords: PRODUCCIÓN AUDIOVISUAL; INTELIGENCIA ARTIFICIAL; HERRAMIENTAS DE INTELIGENCIA ARTIFICIAL